Frequency of Distal Sensory Polyneuropathy among Diabetics in Parakou in 2012 - Adoukonou, Thierry; Kouna-Ndouongo, Philomène; Sourokou Boni, Justine; Imorou, Abdoulaye; HOUINATO, DISMAND STÉPHANE (My University, 2015)
Background: The distal sensory polyneuropathy (DSP) was more frequent among diabetics, although its determinant was not well known among diabetics in Benin. Objective: We aimed to assess the frequency of DSP and its determinants among diabetics at Parakou. Methods: It was a cross-sectional study carried out from 1 March to 31 August 2012 and included 336 diabetics followed at the diabetes unit of Parakou hospital. The diagnosis of DSP was based on DNS (Diabetic Neuropathy Score) criteria and other criteria. All data concerning the diabetes mellitus were recorded. We used Epi-Info and SPSS 16.0 software to perform analysis. Results: They were 187 females (56.0%) with the mean age of 54.9 ± 10.9 years. 298 patients fulfilled criteria for DSP; the overall prevalence of DSP was 88.7%. The main associated factors in multivariate analysis were treatment duration of diabetes more than 4 years: OR = 36.7 [4.0 - 336.9]; the elevated glycaemia: OR = 3.1 [1.4 - 7.1]; the activity with high income: OR = 0.2 [0.0 - 0.8]; the ethnicity: nagots/fon: OR: 3.7 [1.4 - 12.5]. Conclusion: Those results suggested the high frequency of DSP among diabetics at Parakou.
Keywords: Polyneuropathy; Diabetics; Parakou